A situação funcional dos professores da rede estadual paulista: problemas de seleção e admissão e dos concursos públicos (1976-2010) - Santos, Edson Segamarchi dos (2012)
The interest of this investigative work focuses on the analysis of model selection and admission of teachers of the State Department of Education Sao Paulo (SEE / SP), defined from the state and federal law, and the last contests of the discipline of Public Education Physics in the period 1976 to 2010. The research objectives are: to analyze the main features that characterize this particular model selection and hiring of teachers; analyze the functional status of its staff of teachers and to identify the possible elements in the model selection and admission that may be associated with quality of education offered in public schools. The analysis of the object, in turn, is held in the light of critical theory of society, the concepts of ideology of technological rationality, semi-formation and bureaucracy. The results obtained in this indicate that the admission of teachers at SEE/SP has not assured the meeting the demands of the public school of São Paulo, both quantitative and qualitative